Control over the utilization of the loan and the pattern of the gendered division of labor in the loan-funded activity: A case of Duterimbere MFI in Rwanda - Mukamana, Liberata (Cogent social sciences, 2017)
Microcredit is believed to promote the low status of women in decision-making when they can control their loan-funded activities. However, the gendered division of labor of the patriarchal societies is known to create gender inequality in the ways women and men participate in their businesses as women are puzzled by sharing their time between productive and reproductive responsibilities. Based on a cross-sectional research carried with the borrowers in Duterimbere MFI in Rwanda, this paper examines the effect of microcredit on the ability of women and men to control over loan use and allocation of income gained from loans. The study findings revealed that in overall there was gender equality in participating in income generating activities and power over economic decision-making. The only indicator of control over loan that showed inequality between women and men was their level of freedom from domination. This gender inequality comes from cultural norms that prohibit the participation of men in household chores. Intervention to promote gender equality in control over loan use must target to promote men’s willingness to lessen women’s reproductive responsibilities.